Corporate governance in emerging markets and its impact on finance performance (2014)
This paper reviews the theoretical framework of Corporate Governance and multiple issues in which it is evaluated such as agency costs, asymmetric information, insider trading, manipulation of earnings, Board of Directors, etc. Finally, it is reviewed the impact of Corporate Governance over cost of equity, capital structure and financial performance.